2023
DOI: 10.1136/ard-2023-224514
|View full text |Cite
|
Sign up to set email alerts
|

2023 EULAR recommendations for the management of fatigue in people with inflammatory rheumatic and musculoskeletal diseases

Emma Dures,
Bayram Farisoğulları,
Eduardo José Ferreira Santos
et al.

Abstract: ObjectivesFatigue is prevalent in people with inflammatory rheumatic and musculoskeletal diseases (I-RMDs) and recognised as one of the most challenging symptoms to manage. The existence of multiple factors associated with driving and maintaining fatigue, and the evidence about what improves fatigue has led to a multifaceted approach to its management. However, there are no recommendations for fatigue management in people with I-RMDs. This lack of guidance is challenging for those living with fatigue and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The European Alliance of Associations for Rheumatology (EULAR) recently funded a taskforce to examine the effectiveness of non-pharmacological interventions for fatigue in inflammatory rheumatic conditions and the resulting systematic review found strong evidence that some interventions are effective. 14 This informed the EULAR recommendations for the management of fatigue 21 and highlighted a need to better understand contextual factors and the mechanisms by which interventions are effective. 7 There is currently no comprehensive understanding of the factors which influence the success of an intervention.…”
Section: Open Accessmentioning
confidence: 96%
“…The European Alliance of Associations for Rheumatology (EULAR) recently funded a taskforce to examine the effectiveness of non-pharmacological interventions for fatigue in inflammatory rheumatic conditions and the resulting systematic review found strong evidence that some interventions are effective. 14 This informed the EULAR recommendations for the management of fatigue 21 and highlighted a need to better understand contextual factors and the mechanisms by which interventions are effective. 7 There is currently no comprehensive understanding of the factors which influence the success of an intervention.…”
Section: Open Accessmentioning
confidence: 96%
“…In 2023, the European Alliance of Associations for Rheumatology (EULAR) published guidelines recommending the regular assessment of patients with rheumatic diseases for fatigue and providing structured management strategies to address fatigue. 8 Notably, the EULAR guidelines focus on non-pharmacological methods such as psychoeducation and physical therapies. In seeking other options to manage musculoskeletal complaints and take control of their disease, complementary and alternative medicines (CAM) are frequently used by patients despite a lack of evidence base behind such a treatment strategy.…”
mentioning
confidence: 99%